Pengaruh Modal, Jumlah Orderan dan Harga Beli terhadap Pendapatan Supplier Sayuran di Desa Baturiti Kabupaten Tabanan - WISNAWA, ANAK AGUNG NGURAH; SARJANA, I DEWA GEDE RAKA; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
The Influence of Capital, Amount of Order, and Buying Price on Vegetable Suppliers Income in Baturiti Village, Tabanan District The existence of Vegetable Suppliers in Bali Province has increased and its distribution has reached all regions in Bali. Suppliers’ job is to supply goods for production on time with a good quality.Price determination between suppliers and farmers tends to fluctuate. This situation creates the possibility for improvement or decline of farmers welfare which could be assessed using the Farmer Exchange Rate. The price fluctuation has an effect on the capital that is spent by the suppliers, as well as the purchase price from farmers to fulfil the vegetable demand and orders from various consumers.This study aims to analyze the influence of capital, amount of order, and buying price on the income of vegetable suppliers in Baturiti Village. This study uses primary data obtained by distributing questionnaires to 10 vegetable suppliers. For secondary data, this study uses literature, such as books, researches, etc .  The data are processed using SPSS and multiple linear regression analysis techniques. Based on the analysis, the variables that have a positive and significant effect on income are capital and amount of orders. On the other hand, the purchase variable has a negative and significant effect for the income of vegetable suppliers in Baturiti Village, Tabanan Regency.